Challenging the two-source hypothesis - Engelbrecht, J. (Neotestamentica, 1996)
In view of the fact that the two-source hypothesis as solution to the synoptic problem is not generally accepted, and further in view of the fact that the proponents of the Griesbach hypothesis are literarily quite active, this article weighs up the two hypotheses against each other, making particular use of two commentaries on Mark which were written by Griesbach proponents, namely Mann (1986) and Riley (1989).